45 Should primary percutaneous coronary intervention be the routine reperfusion strategy in octogenarians and non-agenarians presenting with ST elevation myocardial infarction?. (9th June 2011) - Showkathali, R; Boston-Griffiths, E; Davies, J; Clesham, G; Sayer, J; Kelly, P; Aggarwal, R
Abstract : Introduction: Primary percutaneous coronary intervention (PPCI) has been established as standard therapy for ST elevation myocardial infarction (STEMI). Very few trials have looked at the outcome of PPCI in elderly patients. Even in trials which claimed to have looked at PPCI in elderly patients such as SENIOR PAMI (Grines, 2005) and TRIANA (Bueno, 2009) the minimum age for inclusion was 70 yrs and 75 yrs respectively. With an ageing population in the western world, about 20% of patients admitted for suspected STEMI are ≥80 yrs. We evaluated the outcome of PPCI in patients ≥80 yrs who were admitted to our unit with STEMI. Methods: Our PPCI service was started in September 2009 and we analysed all the patients who were ≥80 yrs presenting to the PPCI service between September 2009 and September 2010 (13 months). Prospectively entered data were obtained from our dedicated cardiac service database system (Philips CVIS). Mortality data were obtained from the summary care record (SCR) database. Follow-up data were obtained from patients' respective district general hospitals and general practitioners medical records. Results: Of the 998 patients who were admitted to our unit for primary PCI for suspected STEMI during the study period, 183 (18.3%) were ≥80 yrs of age. After excluding 51 patients (27.9%) who did not undergo PPCI, we included 132 (70.1%) patients for analysis. Of those who were included in the study (n=132, 63 female), the mean age was 85±3.95 yrs (range 80–99 yrs, median 85 yrs). There were 20 diabetics (15.2%) and 39 (29.5%) had previous myocardial infarction. Ten patients (7.6%) were in cardiogenic shock on arrival of which 9 (90%) had an Intra aortic balloon pump (IABP). The infarct related vessel was the right coronary in 42.4% and left anterior descending in 37.1%. Drug eluting stents were used in 40.2% of patients. In-hospital and 30-day mortality was 14.4% and 19.7% respectively. There was a significant difference in the mortality between patients age <80 yrs and those ≥80 yrs (Abstract 45 figure 1 ). In patients ≥80 yrs, mortality and bleeding risk increased markedly with advancing age (Abstract 45 table 1 ). Conclusion: This study clearly demonstrates a significant mortality difference between patients aged <80 yrs and those ≥80 yrs treated with PPCI. Our 30-day mortality outcome in patients ≥80 yrs (19.7%) was similar to the subgroup analysis of the PPCI arm in similar SENIOR-PAMI patients (19%). In the same analysis, the thrombolytic group had a lower (16%) mortality. Further studies are required to determine whether PPCI should be routinely used in very elderly patients presenting with STEMI.